Cold War in the Balkans : American Foreign Policy and the Emergence of Communist Bulgaria 1943-1947 - Boll, Michael M., 1938- (Book collections on Project MUSE., 1984)
As World War II drew to a close, the United States and the Soviet Union began to maneuver for position in postwar Europe, in the first exploratory moves of what would soon become a worldwide contest for power and prestige. In Bulgaria, Michael Boll finds a unique vantage point for study of the processes of international politics during these years of the emergence of the Cold War. Bulgaria, he writes, was to assume a significance for both the United States and the Soviet Union greater than that small nation's intrinsic importance to either Great Power. Bulgaria had joined the Axis -- under pres.